Application of artificial liver in immune-related liver injury induced by immune checkpoint inhibitor: Case reports and review of the literature - Li, Xuewei; Ji, Lina; Li, Xiaofang; Sun, Dong; Yang, Wenhui (Frontiers in Immunology, 2022)
The use of immune checkpoint inhibitors (ICIs) can improve survival of patients with malignant tumors, however, the ICI treatment is associated with unpredictable toxicity as immune-related adverse effects (irAEs). Here we report two cases of metastatic malignant gastrointestinal tumors where severe immune-mediated hepatotoxicity (IMH) developed, characterized by liver failure, after the ICI therapy. Through a strong immunosuppressive treatment and a non-biological artificial liver and supportive treatment, the liver function was restored in both cases, and the anti-tumor treatment effect was guaranteed. These results showed that the non-biological artificial liver could be capable of improve prognosis during the ICI therapy.